Effect of Plant Protein on Blood Lipids: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 12 (20th December 2017) - Li, Siying S.; Blanco Mejia, Sonia; Lytvyn, Lyubov; Stewart, Sarah E.; Viguiliouk, Effie; Ha, Vanessa; de Souza, Russell J.; Leiter, Lawrence A.; Kendall, Cyril W. C.; Jenkins, David J. A.; Sievenpiper, John L.
Abstract : Background: There is a heightened interest in plant‐based diets for cardiovascular disease prevention. Although plant protein is thought to mediate such prevention through modifying blood lipids, the effect of plant protein in specific substitution for animal protein on blood lipids remains unclear. To assess the effect of this substitution on established lipid targets for cardiovascular risk reduction, we conducted a systematic review and meta‐analysis of randomized controlled trials using the Grading of Recommendations Assessment, Development, and Evaluation system. Methods and Results: MEDLINE, EMBASE, and the Cochrane Registry were searched through September 9, 2017. We included randomized controlled trials of ≥3 weeks comparing the effect of plant protein in substitution for animal protein on low‐density lipoprotein cholesterol, non–high‐density lipoprotein cholesterol, and apolipoprotein B. Two independent reviewers extracted relevant data and assessed risk of bias. Data were pooled by the generic inverse variance method and expressed as mean differences with 95% confidence intervals. Heterogeneity was assessed (Cochran Q statistic) and quantified (I 2 statistic). The overall quality (certainty) of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation system. One‐hundred twelve randomized controlled trials met the eligibility criteria. Plant protein in substitution for animal protein decreased low‐density lipoprotein cholesterol by 0.16 mmol/L (95% confidence interval, −0.20 to −0.12 mmol/L; P <0.00001; I 2 =55%; moderate‐quality evidence), non–high‐density lipoprotein cholesterol by 0.18 mmol/L (95% confidence interval, −0.22 to −0.14 mmol/L; P <0.00001; I 2 =52%; moderate‐quality evidence), and apolipoprotein B by 0.05 g/L (95% confidence interval, −0.06 to −0.03 g/L; P <0.00001; I 2 =30%; moderate‐quality evidence). Conclusions: Substitution of plant protein for animal protein decreases the established lipid targets low‐density lipoprotein cholesterol, non–high‐density lipoprotein cholesterol, and apolipoprotein B. More high‐quality randomized trials are needed to improve our estimates. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02037321.